2017
DOI: 10.3389/fnins.2017.00457
|View full text |Cite
|
Sign up to set email alerts
|

Inter-individual Relationships between Sympathetic Arterial Baroreflex Function and Cerebral Perfusion Control in Healthy Males

Abstract: Maintenance of adequate cerebral perfusion during normal physiological challenges requires integration between cerebral blood flow (CBF) and systemic blood pressure control mechanisms. Previous studies have shown that cardiac baroreflex sensitivity (BRS) is inversely related to some measures of cerebral autoregulation. However, interactions between the sympathetic arterial baroreflex and cerebral perfusion control mechanisms have not been explored. To determine the nature and magnitude of these interactions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…One theoretical possibility is that to help maintain CBF when cerebral autoregulation is impaired, tighter regulation of blood pressure is necessary to ensure adequate perfusion of the brain. Several previous studies have found an inverse relationship between baroreflex and cerebral autoregulation in healthy young individuals [ 48 50 ]. Based on our findings this same relationship is true for Veterans with GWI since those with the lowest ARI values had the highest baroreflex transfer function gains ( Fig 4B ).…”
Section: Discussionmentioning
confidence: 99%
“…One theoretical possibility is that to help maintain CBF when cerebral autoregulation is impaired, tighter regulation of blood pressure is necessary to ensure adequate perfusion of the brain. Several previous studies have found an inverse relationship between baroreflex and cerebral autoregulation in healthy young individuals [ 48 50 ]. Based on our findings this same relationship is true for Veterans with GWI since those with the lowest ARI values had the highest baroreflex transfer function gains ( Fig 4B ).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than interpretation in a finalistic view, a mechanistic approach has been favored to explain the inverse correlation, linking better CA to enhanced cerebral vasomotor tone due to the increased sympathetic activity associated with diminished BRS ( 7 ). A finalist view, however, cannot be excluded and can be based on the theory of the physiological system complexity states that the structure is optimally configured to support its functions ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In naturally cycling women, enhanced sympathetic baroreflex sensitivity and an increased blood pressure response to hypercapnia exists in the HH menstrual phase compared to the LH menstrual phase (Edwards et al, 1996; Minson et al, 2000b). Furthermore, sympathetic baroreflex sensitivity is negatively associated with dCA, such that less effective dCA is associated with increased sympathetic baroreflex sensitivity and vice versa (Nasr et al, 2014; Tzeng et al, 2010; Witter et al, 2017). Therefore, an enhanced sympathetic influence during hypercapnia in the HH menstrual phase of naturally cycling women may be responsible for the reduced LF dCA observed in the current study.…”
Section: Discussionmentioning
confidence: 99%